An approximate method to compute a sparse graph for traveling salesman problem. Issue 12 (15th July 2015) - Wang, Yong
Highlights The foundation of frequency graph is given for travelling salesman problem. The frequency graph is computed with the OP4s and time complexity is O(n4). The frequency threshold is derived to make the frequency graph sparse. The experiments show the search space of the best solution is reduced a lot.